Variations in DNA methylation and the role of regulatory factors in rice (Oryza sativa) response to lunar orbit stressors - Du, Xiaohui; Zhang, Yan; Zhang, Meng; Sun, Yeqing (Frontiers in Plant Science, 2024)
To investigate the variations in DNA methylation under deep space flight conditions, this study examined rice seeds carried by the Chang'e-5. After 23 days of lunar orbit flight, the samples were planted in an artificial climate chamber and subjected to transcriptome and DNA methylation sequencing during the tillering and heading stages. The methylation patterns in the rice genome exhibit variability in response to lunar orbital stressors. DNA Methylation alters the expression and interaction patterns of functional genes, involving biological processes such as metabolism and defense. Moreover, we utilized single sample analysis methods to analyze the gene expression and interaction pattern of different rice individuals. The genes exhibiting changes at the transcriptional and methylation levels differ among different plants. However, these genes regulate consistent biological functions, with a primary emphasis on metabolic processes. Finally, through single-sample analysis, we identified a set of miRNAs induced by lunar orbital stressors that potentially target DNA methylation regulatory factors.